2018
DOI: 10.1038/s41598-018-34020-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of clinical strains of Pseudomonas aeruginosa strains isolated from different geographic sites

Abstract: The large and complex genome of Pseudomonas aeruginosa, which consists of significant portions (up to 20%) of transferable genetic elements contributes to the rapid development of antibiotic resistance. The whole genome sequences of 22 strains isolated from eye and cystic fibrosis patients in Australia and India between 1992 and 2007 were used to compare genomic divergence and phylogenetic relationships as well as genes for antibiotic resistance and virulence factors. Analysis of the pangenome indicated a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
85
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 87 publications
17
85
2
Order By: Relevance
“…These components are important for interaction of a bacterium with external environments including other species or hosts and hence are under continuous selection pressure (58-61). The pvdE and fliC orthologs have been shown to vary greatly between different strains of P. aeruginosa (62). The replacement islands may contribute to higher virulence in PA34 although this needs to be tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These components are important for interaction of a bacterium with external environments including other species or hosts and hence are under continuous selection pressure (58-61). The pvdE and fliC orthologs have been shown to vary greatly between different strains of P. aeruginosa (62). The replacement islands may contribute to higher virulence in PA34 although this needs to be tested.…”
Section: Resultsmentioning
confidence: 99%
“…P. aeruginosa strain PA34 (referred to as PA34 hereafter) is a multi-drug resistant microbial keratitis isolate which is resistant to gentamicin, imipenem, ciprofloxacin and moxifloxacin. Analysis of its draft genome revealed that PA34 belongs to sequence type 1284 based on multi-locus sequence typing and carried at least 12 acquired resistance genes and possessed the exoU gene (11), an important effector gene in the pathogenesis of microbial keratitis (12). A class I integron (In 1427 ) that carries two antibiotic resistance genes has been shown to be integrated into a Tn3-like transposon carried by PA34 (13).…”
Section: Introductionmentioning
confidence: 99%
“…Integrons were located using Integron finder v1.5.1. The genes possessed by strains 198 and 219 were then compared to those from other ST308 isolates that had been previously examined [6].…”
Section: Methodsmentioning
confidence: 99%
“…For example, P. aeruginosa isolated from water sources can also be isolated from cystic fibrosis patients [4]. Only a few studies have identified clones of ocular isolates of P. aeruginosa [5, 6]. Five multi-drug resistant P. aeruginosa isolates from corneal infections have been reported to be clonal and of sequence type 308.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation